Etyczne determinanty zarządzania ośrodkami szkolenia kierowców w świetle zmian prawnych obowiązujących od 2013 r. - Żuraw, Paweł (Annales. Etyka w Życiu Gospodarczym, 2014)
From 19th January 2013 there have been changes in the operation of driver training centres due to the legislation regarding vehicle drivers coming into force. Changes related to the conduct of driving schools concern four major areas. The first one is a new form of enrolment on driving courses by candidates for drivers, which is done by using the so-called Profile of Candidate for Driver (PCD) generated by the county authorities. The second aspect is the new formula of the theoretical state examination. The third issue is the introduction of cash registers for the operators conducting drivers’ education. The fourth feature is the introduction of new categories of the driving license, in particular a category including two-wheeled vehicles. The existing regulations, as well as the huge competition in the market, have contributed to the fact that the activity of training of candidates for drivers has been dominated by the principle according to which the service must be performed in a cheap and fast way. It automatically translates into the low quality of training and the disregard of procedural steps associated with it. In practice, the lack of adequate control on the part of the state is the reason for the fact that driving has become an arbitrary function based on ruthless marketing and low-cost services. In this situation, ethical dilemmas arise that, in the author’s opinion, will not necessarily be resolved by the new legal standards for drivers.